If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x2+18x-15=11x-10
We move all terms to the left:
x2+18x-15-(11x-10)=0
We add all the numbers together, and all the variables
x^2+18x-(11x-10)-15=0
We get rid of parentheses
x^2+18x-11x+10-15=0
We add all the numbers together, and all the variables
x^2+7x-5=0
a = 1; b = 7; c = -5;
Δ = b2-4ac
Δ = 72-4·1·(-5)
Δ = 69
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:x_{1}=\frac{-b-\sqrt{\Delta}}{2a}x_{2}=\frac{-b+\sqrt{\Delta}}{2a}x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(7)-\sqrt{69}}{2*1}=\frac{-7-\sqrt{69}}{2}x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(7)+\sqrt{69}}{2*1}=\frac{-7+\sqrt{69}}{2}
| 5(2p+7)=120 | | 965000/x=1.75 | | 06x=18 | | 9z+102=103 | | s6+20=188 | | 20+4b=1/3b+5.28 | | a/4-6=16 | | (x-2)/3=12 | | m^{2}+24m+63=0 | | -4x+1=-6x+10 | | b/3b=5(2-b)-4(1-3b)* | | 3x-8+x=4x-8 | | 4x-8+x=4x-8 | | 6t=42t= | | (x-3)/5+4=0,2x+6 | | 5x+17=11x-5 | | 6r+11=3r+2* | | 3x-2=12x-93 | | 2(n+1)=8n-1 | | 5x+36=12x+1 | | 4(6x–7)=144 | | 4(m+2)=6m-3 | | 3x-11=3x-1 | | 8x-37=3x-7 | | 3(x-5)=7+12 | | 2x−1=4x+2 | | 3-2x=0,333333333333333333333333333333333(x+2) | | -5+4g+g=10 | | 3-2x=0,33(x+2) | | 3-2x=(1/3)(x+2) | | -24.4b=14.4 | | 18-4a=5a |